The Impact of Hearing Loss on Executive Function Skills - Marrodan, Elisa; de Diego-Lázaro, Beatriz (Revista de Investigación en Logopedia, 2025)
Children with hearing loss who use cochlear implants might show executive function (EF) difficulties. However, it is unclear whether these challenges exist in children with lower degrees of hearing loss such as children who use hearing aids. The goals of this study were to investigate how the degree of hearing loss affects EF and to identify predictive factors of EF. A total of twenty-six hearing children, 16 children with hearing aids, and 15 with cochlear implants between 4 to 8 years old completed auditory, vocabulary, and direct and reported EF measures. ANOVAs revealed significant differences in inhibitory control by auditory status (direct Stroop interference effect measure). Children with hearing loss (users of cochlear implants or hearing aids) showed poorer inhibitory control than normal hearing peers. The regression analyses revealed that, after controlling for demographic factors, the age at first-word production was a significant predictor of EF measures. As a conclusion, any degree of hearing loss could negatively impact EF abilities, specifically inhibitory control. The age at first-word production is an easy-to-get measure and could be used as a predictor EF in children with hearing loss.
Keywords: executive functions; hearing loss; cochlear implants; hearing aids